The Relantionship between Workload and Work Fatigue of Health Workers - Sari, Dian Purnama; Aidha, Zuhrina; Susilawati, Susilawati (GLOBAL HEALTH SCIENCE GROUP, 2024)
This study aims to explore the relationship between workload and work fatigue among health workers at Puskesmas Sei Balai, Batu Bara Regency. Data was collected from 46 respondents consisting of doctors, nurses, midwives, analysts, nutritionists, and public health workers. This study used a quantitative approach with a cross-sectional research design. The sample consisted of 46 health workers at the Sei Balai Health Center. Data was collected through questionnaires that measured workload levels and burnout. Statistical analysis was performed using the Chi-Square test and Fisher's exact test. The results showed that heavy workload was positively correlated with high work fatigue. This shows the importance of effective workload management to reduce the risk of burnout among health workers. The implications of this research can be used to devise better workload management strategies at Puskesmas Sei Balai and encourage further research in this domain. Based on the results of the study obtained p (p-value) = 0.00 (p < 0.05) that there is a relationship between workload and work fatigue of health workers at the Sei Balai Health Center, Coal Regency.